Recent research and development programs for infrastructures maintenance, renovation and management in Japan. Issue 1 (2nd January 2020) - Fujino, Yozo; Siringoringo, Dionysius M.
Abstract: New research and development program named "Infrastructure maintenance, renovation and management" was started in 2014 under the Council of Science, Technology and Innovation (CSTI)'s Strategic Innovation Program (SIP) of Japan. The 5-year program covers various subjects of infrastructure maintenance with key technologies in condition assessment using non-destructive testing, monitoring and robotics, long-term performance prediction, development of durable high-quality of material for repair and replacement, and management of large amount of bridges and other infrastructure data using advanced information and communication technologies (ICT). The program consists of about 60 research projects involving universities, government research institutes and industries. This initiative is designed as an example for efficient bridge and infrastructure maintenance by reducing the burden of maintenance works and cost. This article describes an overview of representative examples and the outcomes of research and development projects under this program.